NOP2‐Mediated m5C Methylation Modification of LMNB2 mRNA Facilitates Colorectal Cancer Progression - Jinling Bi; Yong Huang; Wentao Hu; Yulong Liu (Cancer Medicine)
ABSTRACT Background Colorectal cancer (CRC) is a leading cause of cancer‐related mortality globally, yet current therapies exhibit suboptimal efficacy with limited prognostic improvement. RNA 5‐methylcytosine (m5C), a posttranscriptional modification, has been implicated in tumorigenesis and progression across malignancies. In our previous study, the m5C methyltransferase NOP2 has been shown to promote proliferation, migration, and invasion of CRC cells, however, the underlying mechanism is still elusive. Methods An integrated multi‐omics strategy was employed, combining transcriptomic sequencing, RNA immunoprecipitation sequencing (RIP‐seq), and methylated RNA immunoprecipitation sequencing (MeRIP‐seq) to explore NOP2‐regulated downstream genes mediating CRC progression via m5C methylation. Functional validation included in vitro and in vivo assays to assess tumor growth and metastasis. Rescue experiments were performed by overexpressing LMNB2 in NOP2‐silenced CRC cells. Results NOP2‐dependent m5C modification of LMNB2 mRNA enhanced its stability, leading to elevated LMNB2 protein levels. This mechanism drove CRC tumor growth and metastasis both in vitro and in vivo. Overexpression of LMNB2 effectively rescued the suppressed malignant phenotypes induced by NOP2 knockdown, confirming LMNB2 as a critical downstream effector. Conclusion NOP2 catalyzes the m5C modification of LMNB2 mRNA to facilitate its stability, which contributes to the elevated LMNB2 protein level and CRC progression, suggesting the potential of NOP2 as a therapeutic target in the development of novel CRC treatment.